Guru Sahabat Siswa: Program Kesehatan Reproduksi bagi Guru - Rieka Esti Saraswati; Ira Paramastri (Jurnal Psikologi, 2013)
The issue of reproductive health is increasing year by year. Proper understanding of reproductive healt his absolutely necessary for students at school. Teacher is one of the important part in learning process, so teachers must have an understanding of reproductive healt has well as sufficient skills to deliver it properly to the students. The purpose of this study is to know the effectiveness of the "Guru Sahabat Siswa” program to increase teachers’ skills to become facilitators in a group discussion on reproductive health theme. The study involves 16 teachers in Junior High School in Yogyakarta. The research will be applied by using the experimental untreated control group design with pretest and post test. This program was proved for improving teachers' skills to be a facilitator in group discussions about reproductive health (F=14,411, p